Effect of the strip spacing on the aerodynamic performance of a high-speed double-strip pantograph. Issue 10 (3rd October 2022) - Dai, Zhiyuan; Li, Tian; Deng, Jian; Zhou, Ning; Zhang, Weihua
Abstract : In this paper, the effect of strip spacing on the aerodynamic performance of a high-speed pantograph with a double-strip is numerically studied using a shear stress transport turbulence model. Seven different strip spacings varied from 100 to 700 mm are considered. The errors in pantograph resistance between numerical simulation and wind tunnel test are within 5% in both knuckle-downstream and knuckle-upstream operating conditions. The drag and lift forces of the strip increase with the strip spacing when the train's running speed is 350 km/h. By considering the two strips individually, it is interesting to find that the lift force on the first strip tends to be stable as the spacing reaches up to 600 mm in both operating conditions, whereas the lift force on the second strip increases continuously with the spacing in the whole range of 100–700 mm. Furthermore, the aerodynamic coefficient of the strip is a nearly constant value at different running speeds, which increases with the strip spacing, suggesting that the relationship between the aerodynamic forces and the spacing of strips obtained in the current study can be extended to any speed level in the range of 200–350 km/h.